Enhancing Tsunami Disaster Risk Reduction Through Improved Evacuation Signage: A Case Study in Gorontalo Village, West Manggarai Regency, East Nusa Tenggara - Alviandi, Donny; Ernalem Bangun; Arifuddin Uksan (Cita konsultindo, 2025)
Labuan Bajo, with its stunning natural beauty, has become one of Indonesia’s premier tourism destinations. The Komodo Islands, exotic beaches, and rich local culture attract visitors from around the world. However, behind this beauty, Labuan Bajo also faces potential natural disaster threats, particularly in several areas such as Gorontalo Village. This village is located in a coastal zone that is vulnerable to tsunami risks. Therefore, it is crucial for the government and local community to improve awareness of tsunami hazards and to prepare effective mitigation measures. To minimize the adverse impacts of a potential tsunami disaster in Gorontalo Village, it is necessary to identify and recommend additional locations for installing tsunami evacuation signs.